Therapeutic Options For Xanthelasma Palpebrarum: Pharmacological Approaches, Surgical Procedures, And Laser Therapy - Joseph Bagasjati Pradika; ⁠Kamal Yasin; Bertrand Revival Hutagalung; Nur Khalisha Yahya; Amin Ibrizatun (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Xanthelasma palpebrarum is a benign skin lesion consisting of a yellowish periorbital plaque due to lipid accumulation, often associated with hyperlipidemia, although primarily an aesthetic complaint. This study aimed to evaluate the effectiveness, complications, and recurrence factors of three main modalities: surgical excision, CO2 laser, and LASIK.₂, and TCA. Using a qualitative systematic literature review approach based on PRISMA, the population included publications from 2021-2025 in Google Scholar, PubMed, and Scopus. The purposive sample consisted of 16 articles (500+ patients) with inclusion criteria of interventional studies and lipid profiles. The PRISMA protocol instrument and thematic content analysis identified patterns of effectiveness through triangulation and MMAT quality appraisal. The results showed that CO laser₂most effective (100% resolution, 13-16% recurrence), followed by surgical excision (3-60%), and TCA 70% for small lesions (25-39% recurrence) with a 33% risk of pigmentation. Conclusions recommend individualization of therapy based on lesion size, skin type, and systemic lipid management to minimize recurrence.